Pendekatan Modern Dalam Manajemen Luka Bakar : Tinjauan Literatur Tentang Balutan Inovatif Dan Terapi Adjuvan - Dearahayu,; Chindy Nur Fadilla,; Dea,; Anggi Suciyana Safitri,; Anyu Tasyaning,; Islaeli, Islaeli (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Burns are a condition that can cause high morbidity due to tissue damage, a high risk of infection, fluid loss, and obstacles to the healing process. Various modern treatment strategies continue to be developed to improve clinical outcomes and minimize complications. Objective: This review aims to evaluate the effectiveness of various innovative dressings and current adjuvant therapies—including hydrogel, next-generation silver sulfadiazine, silver nanoparticles, and alginate–zeolite biomaterials—in accelerating burn wound healing. Methods: The method used is a literature review method by searching articles using the PubMed, Google Scholar, and ScienceDirect databases with keywords burn injury, hydrogel dressing, silver sulfadiazine, silver nanoparticles, alginate hydrogel, and adjuvant therapy, limited to publications from 2020-2025 and filtered based on certain inclusion criteria. A total of eight selected articles were then analyzed thematically. Results: The results indicate that modern dressings and adjuvant therapies provide superior clinical outcomes compared to conventional methods, including accelerated re-epithelialization, reduced infection, and improved new tissue quality. Conclusion: Overall, the use of biomaterials and nanomedicine technology can be considered more effective in supporting burn wound healing and is worthy of consideration as a recommendation in clinical practice